Sistem Informasi Geografis Pemetaan Sebaran Alumni: Sistem Informasi Geografis Pemetaan Sebaran Alumni Pada STMIK STIKOM Indonesia - Adi Panca Saputra Iskandar; I Kadek Dwi Gandika Supartha (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2019)
Alumni data that has been stored is underutilized where this condition is called